Livable city one step towards sustainable development - Farzaneh Sasanpour (Journal of Contemporary Urban Affairs, 2017)
Cities are the engines of economic growth. According to the United Nations, Today the global urban population is expected to reach 3 billion to 5 billion (61 percent) by 2030. The industrial revolution and the resulting economic-social changes led to the transformation of residential patterns and living patterns. Due to the increasing development of cities and its problems, the theory of sustainable development followed by the approach of the livable city was considered. Livable city environment with good planning is an attractive and safe environment for life, work and development, including good governance, competitive economy, high quality of life and environmental sustainability. The results indicate that the social, economic and environmental aspects of the livability of the city of Arak are moderate and unfavourable. Also, the results of the Topsis model, which is a multi-criteria and decision-making model, show that in the environmental dimension of the region two with a score of 0.6859 and in the social dimension of the region of three with a score of 0.92 and in the economic dimension of the region three with a score of 1, the highest rank Have won. As a result, the city of Arak ranked 58th, is not livable and of the three city areas, zone 3 is closer to the surface of livable. And this process will not be in the path of sustainable development.